Peran Program KKN Mengajar dalam Meningkatkan Motivasi Belajar Siswa di SDN Rowobranten, Kendal - Muhammad Ainun Na’im; Risma Nafakhatus Sakhariyah; Fazsya Tatra Khalia (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
This research aims to analyze the role of the KKN Teaching Program in increasing student learning motivation at SDN Rowobranten, Kendal. The KKN Mengajar program, which involves students in service and teaching activities, was implemented as an effort to overcome low learning motivation among elementary school students. Using a mixed-methods approach, data was collected through surveys, interviews, and classroom observations over a three-month period. The research results showed a significant increase in student learning motivation, which was demonstrated by increased attendance, active participation in class, and enthusiasm for the learning process. Additionally, qualitative feedback from teachers and students shows that the KKN Mengajar Program creates a more dynamic and interactive learning environment, and encourages positive attitudes towards education. This research concludes that the KKN Mengajar Program has an important role in increasing student learning motivation and recommends the continuation of this program in similar educational settings to achieve a broader impact on student achievement and engagement.